Mitigation of the Wear Failure of Ti-6al-4v Dental Implant Using Natural and Artificial Ageing Treatment - Bawa, M. A.; Umaru, O. B.; Abdulwahab, M.; Balogun, T.; Abdulazeez, W. S. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2021)
Ti-6Al-4V alloy has been in use as dental implants due to its favourable mechanical properties but wears off over a period of time in the oral cavity. Therefore, this research aimed at using natural and artificial ageing to mitigates the wear failure of Ti-6Al-4V dental biomedical implant. The as received Ti-6Al-4V alloy was sectioned under flowing cooling conditions to 1.4mm x 1.4mm x 0.3mm and then heat treated. The heat treatment involves solution heat treatment at 960oC for 1 hour followed by quenching in warm water at 60oC. After this stage, some of the samples undergo natural ageing for 24 hours, while others were further artificially aged to 480oC with varying soaking times of 2, 4, 6 and 8 hours followed by air cooling. Wear test was conducted at varying loads of 4N and 8N, linear speed of 13.12 cm/s and a dwell time of 30 minutes. The result showed that an increase in ageing time leads to a decrease in wear rate of the alloy for both loads. Also, the samples that were further artificially aged had more wear resistant than the naturally aged samples due to formation of precipitates which are homogenous with the matrix. The minimum wear rates of 0.0114 mm3/N/m and 0.0152 mm3/N/m was obtained at 4 and 8N loads respectively. Therefore, it was established that natural and artificial ageing combined can be employed to enhance the wear resistance of Ti-6Al-4V alloy for use in biomedical applications.